Perbandingan Metode AHP dan ANP Pemilihan Presiden Tahun 2024 Generasi Milenial Politeknik Negeri Cilacap - Syafirullah, Lutfi; Maharrani, Ratih Hafsarah; Bahroni, Isa; Vikasari, Cahya (Explorer, 2024)
The Presidential Election is one of the key elements in democracy which is regulated by the 1945 Constitution of the Republic of Indonesia (UUD 1945). General elections (elections) in Indonesia are held every five years, and the people have the right to vote to elect a presidential candidate who they consider worthy of leading the country during the next term of office. The Presidential election process involves various stages, including nomination by political parties or individuals, political campaigns, debates between candidates, and the voting or election stage. The presidential election (presidential election) is held simultaneously with the legislative election. It is important to note that elections are the foundation for democratic governance, ensuring the active participation of the people in determining the direction and leadership of the country. The Presidential Election in Indonesia is a manifestation of the implementation of democratic principles in the country's political system. The AHP (Analytic Hierarchy Process) method and the ANP (Analytic Network Process) method are methods that can be used in making decisions. A method developed by mathematician Thomas L. Saaty to help solve very complex problems by breaking down various decisions into several smaller criteria. The AHP and ANP methods can overcome assessments based on subjective viewpoints and personal preferences, and transform them into weights with consistent and rational values. Super Decisions is a tool developed specifically to support AHP and ANP calculation applications. Super Decisions provides useful tools in analyzing and processing comparison tables, performing consistency calculations, and assisting in AHP and ANP based decision making.